Konstruksi Sosial Media Bagi Gen Z Dalam Menentukan Tipe Pasangan Ideal Untuk Menjalin Hubungan Asmara - Ramadhani, Fitriah; Tenri Awaru, A. Octamaya; Haris, Hasnawi (Universitas Lambung Mangkurat, 2026)
This study aims to understand how social media shapes the social construction of Generation Z (Gen Z) in determining the ideal type of partner for a romantic relationship. Using a qualitative approach with phenomenological methods, this study explores the subjective meanings that Gen Z has towards their experiences interacting with social media, especially platforms such as TikTok and Instagram. The results show that social media plays a significant role in shaping perceptions, expectations, and standards of romantic relationships among Gen Z. The representation of aesthetic and harmonious relationships in the digital world gives rise to an often unrealistic idealization of partners, and shifts traditional values to values based on aesthetics and social recognition. However, this construction also gives rise to challenges such as communication anxiety, the phenomenon of phubbing, digital social pressure, and a mismatch between the image of relationships in the media and reality. Thus, social media functions dually as a means of identity formation and at the same time a source of psychological pressure in the process of choosing a partner.